The E-COMMERCE TRANSACTIONS IN SHARIA ECONOMICS - Arie Sulistyawan (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mmojokerto, 2025)
Advances in telecommunications, information and computer technology have caused changes in culture and the demands of daily life, thus giving birth to new relationship patterns, including in the business world. One of the mainstay media is through e-commerce (electronic commerce). There is growing concern about e-commerce transactions, especially among Islamic communities in Indonesia, both from a security perspective and a sharia perspective. This paper aims to analyze e-commerce transactions in sharia economics. The results of the analysis concluded that technically the transaction, whether in the form of buying and selling services or goods, if the goods are delivered securely because they are non-digital, then e-commerce transactions can be analogous to buying and selling al-salam, which has been prescribed since the beginning of Islam. through the Sunnah of the Prophet Saw. The use of e-commerce in Indonesia is permitted as long as both parties understand each other. This article is also to provide general guidance for e-commerce users in running their business.